A two component red blood cell model for single cell mechanic - Ahmad, Ida Laila (2015)
This work presents the deformation of red blood cell (RBC) as it travels in a microchannel using a theoretical model. The developed model predicts the deformation experienced by the RBC when exposed to shear stresses (fluid) as a function of mechanical properties. RBC is known to be a biconcave disk and is modeled as a liquid enclosed with a solid membrane. Therefore it is appropriate to model the RBC as a two component models consists of membrane and cytoplasm. The membrane, assumed to behave as an nearly incompressible material shows hyperelastic response to bending and shearing while the cytoplasm exhibits homogeneous Newtonian fluid properties. The model parameters were determined from the experimental measurements and comparison were made. Agreement in terms of hyperelasticity, deformation rate and stress distribution were found with previous researches.